Inadequate Notice of Hearing for Environmental Report Review Committee January 6, 1999, Pertaining to Item No. 3 (Oxnard Airport) - Richard J. Maggio:::::: (1998)
Correspondence discussing a notice of hearing which did not have any reference to an update of the Oxnard Airport Master Plan. Includes the notice of hearing with the agenda of the meeting.